Bioassay-guided Isolation and Identification of Antifungal Compounds from Seeds of Swietenia Macrophylla King - Azhari, H. Nour; Mohammed, Sulieman; M. M., Yusoff; Nour, A. H.; Mazza, M. Adam (AENSI Publishing, 2016)
Swietenia macrophylla King, a plant used extensively in many countries for medicinal purposes. The objective of the present study was to investigate in vitro antifungal activity of the extract as well as bioassay-guided isolation and identification of compounds from most active fraction of S. macrophylla seeds. In the antifungal assay, three clinical fungal strains; namely, Aspergillus flavus, Candida albicans and Aspergillus niger were tested by disc diffusion method. Solvent partitioning followed by Preparative High Performance Liquid Chromatography (prep-HPLC) of the most active fraction afforded four known limonoids and identified by spectroscopic techniques including Fourier Transform Infrared Spectroscopy (FTIR), Mass Spectrometry (MS) and Nuclear Magnetic Resonance Spectroscopy (NMR) analyses. The compounds were: swietenolide (1), proceranolide (2), 3-O-tigloyl-6-O-acetylswietenolide (3) and swietenine acetate (4). Among the fractions, ethyl acetate was the most dominant and effective fraction. Moreover, three compounds (1-3) showed moderate to weak activity, whereas all tested organisms completely resistant to compound 4 and no inhibition zone was observed. On overall, among the three active compounds; compound 1 showed more potent activity than other compounds against all tested organisms.